(Post-)coloniality and intellectuals in the Maghreb: autonomy, tradition and modernity in Abdallah Laroui and Mohammed Abed Al-Jabri - Oliveira, Jessica da Silva Correia de (Universidade Estadual Paulista / UNESP, 2017)
The popular uprisings that occurred in parts of North Africa and Middle East, as well as the plurality of issues that were raised thereafter, led to a questioning about the role of the intelligentsia in the scenario of these societies. Considering this questioning and context as starting points, the main aim of the article is to retrieve elements of one of the central debates in the so-called post-colonial maghrebi thought: the tradition x modernity debate. The aim is also to contextualize this debate specifically in the discussion about politics of identity and imagination surrounding the notion of community in its many different expressions, especially regarding the search for autonomy and the possibilities of modernization available for these societies – and the limits that emerge in this sense. To turn this possible, the reflections of two intellectuals considered as exponents of contemporary maghrebi thought – Abdallah Laroui and Mohammed Abed Al-Jabri – are converted into the primary substract for analysis. Thus, the research is based predominantly on a spatial and authorial delimitation.